Effect of torrefaction on the physicochemical properties of pigeon pea stalk (Cajanus cajan) and estimation of kinetic parameters - Singh R.K.; Sarkar A.; Chakraborty J.P. (My University, 2025)
Torrefaction of biomass is an important preprocessing step which increases energy density and higher heating value. Torrefaction of pigeon pea stalk has been carried out in a tubular quartz reactor at different temperatures under nitrogen atmosphere. DT-TGA data have been used to predict the pyrolysis behavior and in estimating kinetic parameters using Arrhenius method. The effect of temperature was more pronounced as compared to residence time on the yield of solid product during torrefaction. Both O/C ratio and H/C ratios have decreased with increase in temperature. There was 28.6% increase in HHV of torrefied biomass at 275 °C and 45 min residence time as compared to raw biomass. There has been increase in energy density for torrefied biomass as compared to raw biomass. Moisture reabsorption, loose and tapped bulk density decreased for torrefied biomass as compared to raw biomass. For pigeon pea stalk Carr Compressibility index has decreased and Hausner Ratio has increased, resulting in lesser compactability and improved flowability respectively for torrefied biomass. Torrefied pigeon pea stalk exhibited better combustible properties. The activation energies of hemicellulose and cellulose have been decreased by 32.5% and 28.2% due to severe torrefaction. The contribution factor for hemicellulose decreased with increasing severity of torrefaction. © 2019 Elsevier Ltd